2023
DOI: 10.1097/tp.0000000000004640
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Modified Oxford Score in Recurrent IgA Nephropathy in North American Kidney Transplant Recipients: The Banff Recurrent Glomerulonephritis Working Group Report

Abstract: Background. The modified Oxford classification mesangial and endocapillary hypercellularity, segmental sclerosis, interstitial fibrosis/tubular atrophy, and the presence of crescents (MEST-C) of immunoglobulin A nephropathy (IgAN) was recently shown to be a predictor of graft failure in Asians with recurrent IgAN. We aimed to validate these findings in a cohort from North American centers participating in the Banff Recurrent Glomerulopathies Working Group. Methods. We examined 171 transplant recipients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…67 The interdisciplinary collaboration in Banff has also been enhanced recently with the recent publication about recurrent IgA nephropathy in the transplanted kidney. 68 It is impressive to see Banff inspiring other classification efforts even as KDIGO 55 inspires Banff. That augers well for human cooperation in our field even as we face AI challenges!…”
Section: Whereto? On To a Bright Futurementioning
confidence: 99%
“…67 The interdisciplinary collaboration in Banff has also been enhanced recently with the recent publication about recurrent IgA nephropathy in the transplanted kidney. 68 It is impressive to see Banff inspiring other classification efforts even as KDIGO 55 inspires Banff. That augers well for human cooperation in our field even as we face AI challenges!…”
Section: Whereto? On To a Bright Futurementioning
confidence: 99%
“… 12 Other previous studies showed that a higher MEST-C score and a lower estimated glomerular filtration rate at the time of biopsy were associated with poor prognosis in patients with IgAN recurrence. 13 Some biomarkers for the prediction of post-transplant IgAN recurrence have been studied, such as IgA and IgA-complexes (IgA-IgG and IgA-soluble CD89), galactose-deficient IgA1 (Gd-IgA1), and anti-Gd-IgA1 autoantibodies, although its clinical application is not entirely known. 14 Graft dysfunction related to recurrence is rare before three years of follow-up.…”
Section: Iga Nephropathymentioning
confidence: 99%
“…17 Sodium-glucose cotransporter-2 (SGLT-2) inhibitors are indicated for native IgAN with proteinuria or impaired renal function, and their use can be considered in cases of post-transplant recurrence. 13 Several glucocorticoid regimens were proposed in clinical for patients presenting proteinuria higher than 0.75–1 g/day despite optimized supportive care. 10 However, the clinical benefit of glucocorticoids in IgAN has not been established.…”
Section: Iga Nephropathymentioning
confidence: 99%